2018
DOI: 10.1002/ecy.2213
|View full text |Cite
|
Sign up to set email alerts
|

Lifting the veil: richness measurements fail to detect systematic biodiversity change over three decades

Abstract: While there is widespread recognition of human involvement in biodiversity loss globally, at smaller spatial extents, the effects are less clear. One reason is that local effects are obscured by the use of summary biodiversity variables, such as species richness, that provide only limited insight into complex biodiversity change. Here, we use 30 yr of invertebrate data from a metacommunity of 10 streams in Wales, UK, combined with regional surveys, to examine temporal changes in multiple biodiversity measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 65 publications
7
46
0
4
Order By: Relevance
“…Although strong evenness effects on ecosystem functioning have been demonstrated in previous regional studies (e.g. Filstrup et al 2014a;Hodapp et al 2015), our study extends these relationships to continental scales (Figs 2 and 3), thereby echoing recent calls to consider measures of biodiversity beyond richness in BEF relationships (Hillebrand et al 2018;Larsen et al 2018). Evenness has been argued to be more sensitive to environmental change than richness because species tend to become rare in communities before becoming extinct (Hillebrand et al 2008;Hillebrand & Matthiessen 2009).…”
Section: Biodiversity Effects Within and Across Trophic Levelssupporting
confidence: 78%
See 1 more Smart Citation
“…Although strong evenness effects on ecosystem functioning have been demonstrated in previous regional studies (e.g. Filstrup et al 2014a;Hodapp et al 2015), our study extends these relationships to continental scales (Figs 2 and 3), thereby echoing recent calls to consider measures of biodiversity beyond richness in BEF relationships (Hillebrand et al 2018;Larsen et al 2018). Evenness has been argued to be more sensitive to environmental change than richness because species tend to become rare in communities before becoming extinct (Hillebrand et al 2008;Hillebrand & Matthiessen 2009).…”
Section: Biodiversity Effects Within and Across Trophic Levelssupporting
confidence: 78%
“…Recent debate surrounding interpretation of static or increasing temporal trends in local species richness and studies demonstrating that these trends may not be sensitive indicators of biodiversity change (Cardinale et al 2018;Hillebrand et al 2018;Larsen et al 2018) justify the need for a more complete understanding of BEF relationships. The focus on species richness as the primary measure of biodiversity has resulted in a poor understanding of the effects of other biodiversity metrics on ecosystem functioning (Wilsey et al 2005;Hillebrand et al 2008;Hillebrand & Matthiessen 2009;Hooper et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Winegardner et al (2017) did not find changes in spatial beta diversity of lake diatoms between 1850 and 2007, even though they had a longer time period examined compared with that in our study. Similarly, Larsen et al (2018) did not find signs of biotic homogenisation when they studied stream macroinvertebrates in 10 streams during 30 yr. However, Wengrat et al (2018) found a decreasing trend in spatial beta diversity of diatom assemblages, but only when they studied eutrophic reservoirs instead of the whole set of reservoirs over the past 60-100 yr.…”
Section: Discussionmentioning
confidence: 95%
“…The trait‐based approaches to appraise the mechanisms behind community resilience can be illustrated using a case study from the Lynn Brianne Stream Observatory (Wales, United Kingdom: see Ormerod & Durance, ). A long‐term time series of benthic invertebrate communities monitored in multiple catchments shows overall stability in taxonomic richness and suggests resilience to environmental changes (Larsen, Chase, Durance, & Ormerod, ). Different responses to environmental change can be inferred from taxonomic and phylogenetic indices (respectively taxonomic richness and taxonomic distinctness, Figure ) because the two metrics show specific variations that can each be linked to specific types of environmental change, involving large flow variations and high temperatures.…”
Section: Framework To Assess Ecosystem Resilience In Management Perspmentioning
confidence: 99%
“…In this case study, a measure of taxonomic richness can indicate the community response in redundancy most clearly, where the phylogenetic diversity provided a strong indicator for recruitment recovery and for selective responses (specialists resistant to heat wave). In conclusion, most studies find that responses are difficult to reveal with single indices and that community‐level aspects of niche breath and specialization often are necessary to analyse over longer time intervals to fully detect and interpret responses of communities to disturbances (Larsen et al, ).…”
Section: Framework To Assess Ecosystem Resilience In Management Perspmentioning
confidence: 99%